Laminar periodic flow and heat transfer in square duct with 30o end-trimmed rectangular winglet - Boonloi, Amnart; Jedsadaratanachai, Withada; Promvonge, Pongjet (Engineering and Applied Science Research, 2014)
A numerical investigation has been carried out to examine laminar flow and heat transfer characteristics in a three-dimensional isothermal wall duct with 30O end-trimmed rectangular winglet. The computations are based on the finite volume method, and the SIMPLE algorithm has been implemented. The fluid flow and heat transfer characteristics are presented for Reynolds numbers based on the hydraulic diameter of the duct ranging from 100 to 2000. To generate vortex flows through the square duct, winglet with an attack angle of 30o are mounted in the square duct. Effects of different flow blockage areas with single pitch length ratios on heat transfer and friction loss are investigated. It is apparent that the main vortex flows created by the 30o end-trimmed rectangular winglet exist and help to induce impinging flows on the wall of the winglet cavity leading to drastic increase in heat transfer rate over the duct. In addition, the rise in the winglet height results in the increase in the friction factor values. The computational results reveal that the maximum thermal enhancement factors for the end-trimmed with BR=0.10 is found to be about 4.10 at Re=2000.